A review on post-operative complications and its care after cataract surgery - Amarjeet, Singh; Pankaj, Sharma; Jyoti, Gupta; Jaya, Sharma (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2016)
A cataract is a clouding of the natural intraocular crystalline lens that focuses the light entering the eye onto the retina. This cloudiness can cause a decrease in vision and may lead to eventual blindness if left untreated. Cataracts often develop slowly and painlessly, so vision and lifestyle can be affected without a person realizing it. Worldwide, cataracts are the number one cause of preventable blindness. Modern cataract surgery, which is the removal of the cloudy lens and implantation of a clear intraocular lens (IOL), is the only definitive treatment for Cataracts often develops slowly with a gradual decline in vision that cannot be corrected with glasses. Common complaints include blurry vision, difficulty reading in dim light, and poor vision at night, glare and halos around lights, and occasionally double vision. Other signs of cataracts include frequent changes in the prescription of glasses and a new ability to read without reading glasses in patients over 55. There are several types of cataract including age related, traumatic, and metabolic. Age related is the most common type and the pathogenesis is multifactorial and not fully understood. A traumatic cataract can occur following both blunt and penetrating eye injuries as well as after electrocution, chemical burns, and exposure to radiation. Metabolic cataracts occur in uncontrolled diabetics, patients with galactosemia, Wilson disease, and Myotonic dystrophy.